National culture and firm financial performance: A mediating role of firm financing decision - Umar Farooq; Jaleel Ahmed; Khurram Ashfaq; Ghias ul Hassan Khan; Shamshair Khan (Cogent Business & Management, 2020)
This study unfolds the role of national culture in determining the firm financial performance through channel of corporate financial policy. Sample size consists of 7623 non-financial sector firms from 13 Asian economies and fixed-effect model applies to estimates the regression. As the findings reveal, countries carrying high scores on power distance, individualism and long-term orientation face the low firm performance due to high transaction cost, agency cost, and problem of information asymmetric in their financing decision. In contrast, corporate firms from high masculine, high uncertainty avoidance and indulgence countries enjoy the better firm performance as these cultures indicate the effort assertive, resolving the uncertainties and co-operative behavior. In brief, the findings of study highlight the importance of national culture and give better insights into how cultural values determine the corporate financing policy which further affects the financial efficiency. It also provides the direct evidence on the effect of cultural values upon financial performance.
Keywords: Z10; G32; G30; 650; Hofstede's six national cultural dimensions; capital structure; firm performance; Asian economies